When a part of “self” dies: On grief and the feeling of loneliness after losing a beloved animal - Płaczek, Aleksandra (Difficult situation in biographies: Volume 9, 2025)
The chapter presents a reconstruction of experiences related to the loss of a beloved animal, using the method of autoethnography. It discusses the differences in grieving the loss of close “people” and “animals,” drawing on personal experiences of losing a cherished pet. These experiences are compared with the mourning process after the loss of close human relationships, with attention to the influence of social and cultural norms on how grief is perceived and expressed. The chapter emphasizes that, despite society’s frequent minimization of the loss of animals, the emotional impact of this grief is as deep and complex as that experienced after the loss of human loved ones.